Three Opportunities for the Future of Juvenile Forensic Assessment - Grisso, Thomas (Criminal justice and behavior, 2019)
Legal and social circumstances now offer the field of juvenile forensic assessment several opportunities to expand its identity, influence, and value to society. These opportunities include (a) conceptualizing an assessment domain called evaluations for developmental sentencing, (b) creating developmental forensic evaluations of emerging adults, and (c) adapting juvenile forensic assessments to the nation’s increasing ethnic and cultural diversity. If successfully attempted, these opportunities could transform juvenile forensic assessment’s identity, reimagining itself as developmental forensic assessment applied to offenders in both juvenile and criminal courts.